Preparation and Coagulation Behavior of a Novel Multiple Flocculant Based on Cationic Polymer, Hydroxy Aluminum, and Clay Minerals. (22nd March 2015) - Zhou, Feng-shan; Wang, Xi; Zhou, Lin; Liu, Yang
Abstract : Cationic polymer, hydroxy aluminum, and clay minerals are three flocculants with different action mechanisms and a more cost-efficient multiple flocculant can be prepared by compositing them through appropriate technology. All of attapulgite (ATP), clay minerals containing magnesium, aluminum, and silicate, are porous environmental mineral material with good absorbability and have found wide applications in industrial sewage treatment. With polyaluminum chloride (PAC), poly(dimethyl diallyl ammonium chloride) (PDMDAAC), and attapulgite (ATP) clay being the main raw materials, multiple flocculant CMHa (liquid) with good storage stability was prepared and its optimized blending mass percent was PDMDAAC of 2%-3%, ATP of 4%–6%, and PAC of 20%–30%. The liquid poly(dimethyl diallyl ammonium chloride) (PDMDAAC) was firstly loaded on solid material in kneader and then mixed in certain proportion with PAC and ATP to prepare solid CMHa convenient for storage and transportation. The optimized mass ratio is PAC : ATP : PDMDAAC = 80 : 10 : 2.4. When this multiple flocculant was used to treat domestic sewage, coal washing sewage, dyeing wastewater, and papermaking wastewater, its equivalent dosage was just 50% of PAC, while overall production cost has been reduced to about 40%, viewing showing broad application prospect.